Pengaruh Karakteristik Individu, Karakteristik Pekerjaan dan Karakteristik Organisasi terhadap Kepuasan Kerja Karyawan Koperasi (Sumber Data Mandiri) Muara Teweh Kalimantan Tengah - Isna Wardana; Hj. Siti Rusidah; Nurul Wahyuni (JURNAL BISNIS DAN PEMBANGUNAN, 2017)
This study aims to examine and analyze the partial whether (1) Transformational Leadership Style significant effect on employee performance, (2) discipline Job significant effect on employee performance, (3) Cultural Organization significant effect on employee performance (4) and test and analyze together (simultaneously) whether Transformational leadership, Discipline Work and Organizational Culture influence on employee performance at the Post Office Palangkaraya in Central Kalimantan.The study population were employees of the Post Office of Palangkaraya in Central Kalimantan numbered as many as 34 people and also became samples taken by sampling saturated. Methods This study uses a quantitative approach. This study uses data analysis techniques Regression. Validity and reliability test using SPSS 21.0 softwere assistance.The results showed that: (1) The test result is known that there is no significant influence of Transformational Leadership Style (X1) on employee performance (Y) partially, by 0.042. (2) The test result is known that there are significant effect Work Discipline (X2) the Employee Performance (Y) partially, by 0.279. (3) The test result is known that there are significant effect Cultural Organization (X3) on employee performance (Y) partially, by 0.634. (4) From the test results it is known that there is no significant influence Transformational Leadership Style (X1), Work Discipline (X2) and Cultural Organization (X3) on employee performance (Y) simultaneously, 0.776. (5) Interpretation of the results of this testing is the constant of 10.225 Keywords: Transformational Leadership Style, Work Discipline, Organizational Culture and Employee Performance.